2007
DOI: 10.3390/12020271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Rigid Polycyclic Derivatives of the Diels-Alder Adduct Tricyclo[6.2.1.02,7]undeca-4,9-dien-3,6-dione

Abstract: Part of our research program concentrates on the discovery of new bioactive compounds prepared either by total synthesis or molecular transformation of compounds with bioactivity profiles. In this work we have focused our interest on chemical transformations of the Diels-Alder adduct tricyclo[6.2.1.0 2,7 ]undeca-4,9-dien-3,6-dione in order to obtain cage-like compounds and derivatives, followed by an evaluation of their biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…This was also observed in attempts to conjugate benzylamine to the 6-keto of the 3-hydroxyltricycloundecane derivative 5 which were unsuccessful even under extreme temperatures, high pressure, and microwave irradiation. The reduction of compounds 7a,b and 9 using sodium borohydride as reducing agent yieldedc ompounds 8 and 10,r espectively.Acomparison of the NMR data for 8 and 10 with that of similar tricyclic keto esters described by Marchand et al that contained an endo-3-dinitrobenzoyloxy group, [30] andb yI to et al,w hich contained an endo-3-trimethylmethoxyphenylcarbonyloxy group, [28] confirmed the structures proposed for 8 and 10 (Scheme 1). Interestingly,o nly the endo-3-benzylamine derivative 8 was obtained from reduction of the isomeric mixture of 7a,b.T his might indicate that we were ablet os electively reduce 7b,o rt hat only the endo-3-benzylamine 8 was isolated from the reactionm ixture.…”
Section: Chemistrysupporting
confidence: 68%
See 4 more Smart Citations
“…This was also observed in attempts to conjugate benzylamine to the 6-keto of the 3-hydroxyltricycloundecane derivative 5 which were unsuccessful even under extreme temperatures, high pressure, and microwave irradiation. The reduction of compounds 7a,b and 9 using sodium borohydride as reducing agent yieldedc ompounds 8 and 10,r espectively.Acomparison of the NMR data for 8 and 10 with that of similar tricyclic keto esters described by Marchand et al that contained an endo-3-dinitrobenzoyloxy group, [30] andb yI to et al,w hich contained an endo-3-trimethylmethoxyphenylcarbonyloxy group, [28] confirmed the structures proposed for 8 and 10 (Scheme 1). Interestingly,o nly the endo-3-benzylamine derivative 8 was obtained from reduction of the isomeric mixture of 7a,b.T his might indicate that we were ablet os electively reduce 7b,o rt hat only the endo-3-benzylamine 8 was isolated from the reactionm ixture.…”
Section: Chemistrysupporting
confidence: 68%
“…[29,30] The treatment of 5 with N-bromosuccinimide resulted in ac losedring bromoether derivative 6 in nearly quantitative yield. [28,31] The structures of compounds 3-6 were confirmed on the basis of their respective melting points, NMR and IR spectra,a nd literature references; [28][29][30][31] they served as precursors for the novel tricycloundecylamined erivatives reported herein.…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations